2005
DOI: 10.1007/s10600-005-0127-6
|View full text |Cite
|
Sign up to set email alerts
|

Arabinogalactan Poly- and Oligosaccharides Modified with 5-Aminosalicylic Acid

Abstract: Arabinogalactan poly-and oligosaccharides from Siberian larch (Larix sibirica L.) were modified with 5-aminosalicylic acid. The chemical composition and certain physicochemical properties were studied. The optimal conditions for preparing the modified compounds were found. These compounds were demonstrated to possess anti-ulcer and anti-inflammatory activity in tests on experimental animals.One of the methods for creating improved forms of medicinal compounds is their modification with natural polysaccharides.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…It has been revealed that oligomeric products show anti-inflammatory and antiulcer activities. Reactions of AG and oxidized AG with some known MS give intermolecular complexes [46][47][48]. Such complexes of AG with 5-aminosalicylic acid show high antiulcer activity, while complexes incorporating 4-aminosalicylic or isonicotinic acid hydrazide demonstrate an antituberculosis effect.…”
Section: Physicochemical and Biological Properties Of Arabinogalactanmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been revealed that oligomeric products show anti-inflammatory and antiulcer activities. Reactions of AG and oxidized AG with some known MS give intermolecular complexes [46][47][48]. Such complexes of AG with 5-aminosalicylic acid show high antiulcer activity, while complexes incorporating 4-aminosalicylic or isonicotinic acid hydrazide demonstrate an antituberculosis effect.…”
Section: Physicochemical and Biological Properties Of Arabinogalactanmentioning
confidence: 99%
“…Such complexes of AG with 5-aminosalicylic acid show high antiulcer activity, while complexes incorporating 4-aminosalicylic or isonicotinic acid hydrazide demonstrate an antituberculosis effect. It has been established that conjugates of AG and products of its modification increase the physiological effect of MS and decrease their toxicity [28,[46][47][48]; for instance, a conjugate of AG (9kDa) 9--Darabinofuranosyladenine-5'-monophosphate was 25-fold more active than the parent compound 9--D-arabinofuranosyladenine (araA) in decreasing the amount of hepatitis B virus, and the toxicity of the complex preparation is much lower than araA [28]. To increase reactivity of AG with MS, the synthesis of conjugates proceeds by bromination, phosphorylation, amination, formation of hydrazides or reaction with NaBH4 [27,33,34].…”
Section: Physicochemical and Biological Properties Of Arabinogalactanmentioning
confidence: 99%